Microwave assisted synthesis of 2-(4-substituted piperazin-1-yl)-1, 8-naphthyridine-3-carbonitrile as a new class of serotonin 5-HT< sub> 3 receptor antagonists - Mahesh, R.; Venkatesha Perumal, R.; Pandi, P.V. (2004)
A series of novel 2-(4-substituted piperazin-1-yl)-1,8-naphthyridine-3-carbonitrile 6 were prepared by microwave irradiation and conventional heating. The intermediate, 2-oxo-1,2-dihydro-1,8-naphthyridine-3-carbonitrile 3, was prepared from 2-aminonicotinaldehyde 1 and ethyl cyanoacetate 2 in the presence of piperidine under solvent free condition. The synthesized compounds were evaluated for 5-HT3 antagonisms in longitudinal muscle-myenteric plexus (LMMP) preparation from Guinea pig ileum against 5-HT3 agonist, 2-methyl-5-HT. Among the compounds tested, 2-(4-allylpiperazin-1-yl)-1,8-naphthyridine-3-carbonitrile 6d showed most favorable 5-HT3 receptor antagonism in the Guinea pig ileum.